Pengaruh Promosi Terhadap Keputusan Pembelian Konsumen pada Motor Yamaha di PT.Hasjrat Abadi Cabang Agusalim Kota Gorontalo - Siti Firgiyanti Adam; Hapsawati Taan; Ramlan Amir Isa (Economic Reviews Journal, 2024)
This research aims to determine the effect of promotions on consumer purchasing decisions on Yamaha motorbikes at PT. Hasjrat Abadi, Agusalim Branch, Gorontalo City. The research approach used is a quantitative research approach. The sample from this research consisted of 93 respondents with sampling using non-probability sampling techniques. And the type of data used is primary data. The data collection technique uses a questionnaire. The data analysis technique used is multiple linear regression. The results of this research can have a positive and significant influence on purchasing decisions. This shows that the t count is 1.031 and the significant value is 0.000<0.05, so it can be stated that there is a significant influence between promotions on consumer purchasing decisions on Yamaha motorbikes. So it can be concluded that promotions have a significant effect on consumer purchasing decisions on Yamaha motorbikes at PT. The eternal desire of the Agussalim branch of Gorontalo City.